The Extracellular Matrix in Digestive Cancer - Worthley, Daniel L. (Springer Netherlands, 2010)
The extracellular components of the cancer microenvironment play a critical role in tumor initiation, progression and invasion. In this review we examine the normal formation and function of the basement membrane and extracellular matrix. We characterize the interactions between the matrix and the epithelium and explore the causes and consequences of the extracellular remodeling that accompanies carcinogenesis. Finally, we address the therapeutic possibilities of incorporating matrix as well as epithelial strategies in the management of digestive cancer.